2020
DOI: 10.1186/s12935-019-1066-9
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of CDX2 alleviates breast cancer by up-regulating microRNA let-7b and inhibiting COL11A1 expression

Abstract: Background: microRNA Let-7 serves as a tumor suppressor by targeting various oncogenic pathways in cancer cells. However, the underlying mechanism of its involvement in breast cancer remains largely unknown. With our research, our endeavor is to explore the role of the CDX2/let-7b/COL11A1 axis in breast cancer cell activities. Methods: Tumor tissues and adjacent normal tissues were collected from 86 patients with breast cancer. Human breast cancer epithelial cell line MCF-7 was treated with over-expressed CDX2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…First of all, 512 robust DEGs between breast tumor tissues and normal breast tissues were identi ed using RRA method. Among them, COL11A1, S100P, LEP and FGF2 are the most signi cant DEGs, which have been reported to be associated with the pathogenesis and development of breast cancer [38][39][40][41]. Functional annotation analysis revealed that the robust DEGs signi cantly enriched in many GO terms associated with proliferation and energy metabolism, such as extracellular matrix organization, extracellular structure organization, mitotic nuclear division, regulation of lipid metabolic process, and glycosaminoglycan binding, which were consistent with published data [42][43][44].…”
Section: Discussionsupporting
confidence: 88%
“…First of all, 512 robust DEGs between breast tumor tissues and normal breast tissues were identi ed using RRA method. Among them, COL11A1, S100P, LEP and FGF2 are the most signi cant DEGs, which have been reported to be associated with the pathogenesis and development of breast cancer [38][39][40][41]. Functional annotation analysis revealed that the robust DEGs signi cantly enriched in many GO terms associated with proliferation and energy metabolism, such as extracellular matrix organization, extracellular structure organization, mitotic nuclear division, regulation of lipid metabolic process, and glycosaminoglycan binding, which were consistent with published data [42][43][44].…”
Section: Discussionsupporting
confidence: 88%
“…Another study in a mouse model of pancreatic cancer suggests that COL11A1 can be activated by the Hedgehog signaling pathway [ 68 ]. In xenograft mouse models of breast cancer, COL11A1 expression is negatively regulated by transcription factor CDX2 and microRNA let-7b and the loss of COL11A1 expression by upregulating CDX2 let-7b suppressed metastasis [ 55 ]. Muscle, intestine and stomach expression 1 (Mist1), a transcriptional repressor can inhibit COL11A1 expression and reverse EMT in a pancreatic cancer mouse model [ 67 ].…”
Section: Col11a1 In Tumor Cell Migration and Metastasismentioning
confidence: 99%
“…Degradation of matrix proteins, such as collagen, may serve as a critical step in the tumour cell invasion of surrounding tissues 40 . Several studies have explored the relationship between COL11A1 and breast cancer cells 41,42 . COL10A1 and COL5A1 have also shown prognostic significance in breast cancer 43,44 .…”
Section: Discussionmentioning
confidence: 99%